A phenomenographic study on language assessment literacy: hearing from Iranian university teachers - Afsheen Rezai (SpringerOpen, 2021)
Abstract This study aims to disclose the Iranian university teachers’ perceptions of the fundamentals of language assessment literacy (LAL). To this aim, using purposive sampling, eighteen university teachers from two Iranian universities were invited to participate in semi-structured interviews. Their viewpoints were audio-recorded, transcribed, and subjected to a phenomenographic analysis. Findings yielded two overarching LAL domains: knowledge (e.g., having an acceptable level of digital LAL, satisfying ethical requirements, benefiting more from performance assessment, considering students’ individual differences, making assessment valid, assuring that tests are reliable, and having an acceptable level of pedagogical content knowledge) and skills (e.g., involving students in assessment, using alternative assessment methods, employing logically traditional assessment methods, informing students about test results, administering tests in standardized ways, using valid grading procedures, and bringing positive wash-back effects). After discussing the results, the study concludes with proposing a range of implications for different testing stakeholders and highlighting some avenues for further research.